Writing Anthropologists, Sounding Primitives : The Poetry and Scholarship of Edward Sapir, Margaret Mead, and Ruth Benedict - Reichel, A. Elisabeth (Book collections on Project MUSE., 2021)
"Writing Anthropologists, Sounding Primitives" offers a contribution to the history of anthropology by synthesizing and applying insights from the history of writing, sound studies, and intermediality studies to poetry and scholarship produced by early twentieth-century U.S.-American cultural anthropologists"--